Interaction of some new 2-(substituted-thio)-quinazolin-4-ones with molybdenum hydroxylases: A pharmacophore prediction - Hussein I. El-Subbagh; Alaa A.-M; Mohamed A. Al-Omar; Fatmah A. Al-Omary (SpringerOpen, 2015)
Background: Molybdenum hydroxylases have been implicated as key oxidative enzymes in some diseases. Methods: Twenty 2-(substituted-thio)-quinazolin-4-one derivatives recently synthesized in our laboratory were examined for their inhibitory activity toward molybdenum hydroxylases. Results and conclusion: The tested quinazolines inhibited both xanthine oxidase and aldehyde oxidase enzymes in a competitive pattern with Ki values range of 66-753 μM. Pharmacophore prediction methodology was used to study the structure requirements of those inhibitors.